Pengembangan Hotel Syariah di Indonesia: Tantangan Yang Dihadapi Hotel Sofyan - Jakarta - Surahman Hidayat; AA Hubur; Najamudin Najamudin (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to analyze the challenges faced by the Sofyan-Jakarta hotel. First, the challenge of human resources, second, the challenge of literacy related to sharia hotels. The research method used is a qualitative method with a descriptive approach. The sources used are primary and secondary data sources. The primary data source was obtained from Mr. Riyanto Sofyan as the Owner of the Sofyan-Jakarta Hotel, and Dr. KH. Surahman Hidayat, MA as the Sharia Supervisory Board of the Sofyan Jakarta hotel. Secondary data sources were obtained from the literature. The data collection method used by the researcher was the interview, observation, and documentation methods. Based on the results of this study, first, the human resource challenges faced by the Sofyan hotel are; the lack of employees who have the ability to manage hotel operations on the one hand as well as mastery of sharia knowledge on the other hand and do not have work motivation as employees on the one hand and as preachers on the other. Then the second challenge is the lack of literacy related to sharia hotels so that the public is not yet able to recognize and distinguish between sharia and conventional hotels. Therefore, researchers recommend that routine weekly, monthly and quarterly training should be conducted for all employees. In addition, there must be cooperation with academics from various universities and Islamic mass organizations such as NU, Muhammadiyah, Persis, etc. in order to increase literacy related to sharia hotels.